Contemporary in-hospital outcomes of chronic total occlusion percutaneous coronary interventions: Insights from the MENATA (Middle East, North Africa, Turkey, and Asia) chapter of the PROGRESS-CTO registry - ÇİNÇİN, AHMET ALTUĞ (My University, 2023)
Chronic total occlusion (CTO) percutaneous coronary intervention (PCI) has been rapidly evolving in different parts of the world. We examined the clinical and angiographic characteristics and procedural outcomes of 1,079 consecutive CTO PCIs performed in 1,063 patients at 10 centers in the Middle East, North Africa, Turkey, and Asia regions between 2018 and 2022. The mean age was 61 ± 10 years and 82% of the patients were men. The prevalence of diabetes (49%) and previous PCI (50%) was high. The most common target vessel was the right coronary artery (51%), followed by the left anterior descending artery (33%) and the circumflex artery (15%). The mean Japanese CTO score was 2.1 ± 1.2 and mean PROGRESS-CTO (Prospective Global Registry for the Study of Chronic Total Occlusion Intervention) score was 1.2 ± 1.0. The technical and procedural success rates were high (91% and 90%, respectively) with a low incidence (1.6%) of in-hospital major adverse cardiac events. The incidence of perforation was 4.6% (n = 50): guidewire exit was the most common mechanism of perforation (48%) and 14 patients required pericardiocentesis (28%). Antegrade wire escalation was the most common crossing strategy used (91%), followed by retrograde approach (24%) and antegrade dissection and re-entry (12%). Median contrast volume, air kerma radiation dose, and fluoroscopy time were 300 (200 to 400) ml, 3.7 (2.0 to 6.3) Gy, and 40 (25 to 65) minutes, respectively. In conclusion, high success and acceptable complication rates are currently achieved at experienced centers in the Middle East, North Africa, Turkey, and Asia regions using a combination of crossing strategies.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KALP VE KALP DAMAR SİSTEMLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; CARDIAC & CARDIOVASCULAR SYSTEMS; Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine; chronic total occlusion; outcomes; percutaneous coronary intervention